2020
DOI: 10.3904/kjim.2019.319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of procedural sequence in same-day bidirectional endoscopy: a systematic review and meta-analysis

Abstract: Background/Aims: To compare the efficacy and safety of procedural sequence in same-day bidirectional endoscopy. Methods: We searched OVID-MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Google Scholar to identify randomized controlled trials that compared the procedural sequences in same-day bidirectional endoscopy, including esophagogastroduodenoscopy (EGD) and colonoscopy. The sedative and analgesic doses required, discomfort and satisfaction scores, procedure time, recovery time, adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…Previous studies on the optimal sequence of BDE using air-insufflated colonoscopy did not show a significant difference in the cecal-intubation time or total procedure time of colonoscopy [ 4 , 7 , 10 , 11 , 12 , 13 ]. In contrast, the current study showed that the EGD-first group had a longer cecal-intubation time and total procedure time.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies on the optimal sequence of BDE using air-insufflated colonoscopy did not show a significant difference in the cecal-intubation time or total procedure time of colonoscopy [ 4 , 7 , 10 , 11 , 12 , 13 ]. In contrast, the current study showed that the EGD-first group had a longer cecal-intubation time and total procedure time.…”
Section: Discussionmentioning
confidence: 93%
“…Post-colonoscopy abdominal pain was associated with the female sex, older age, an unsedated procedure, a longer procedure time, the use of air instead of carbon dioxide (CO 2 ) and the timing of assessment [24,27,28]. Although a recent metaanalysis [13] reported lower discomfort scores after both procedures in the EGD-first group, the conclusion could be misleading because the analysis mostly included studies evaluating discomfort during the procedures, and the lower discomfort score actually occurred during EGD, which was correctly reported by another meta-analysis [7] (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In same-day BDE, EGD first followed by colonoscopy is the favored order of the procedures due to lower discomfort scores in earlier meta-analysis. 5 Abdominal bloating caused by colonoscopy first in BDE might reduce tolerance to subsequent EGD. 12 In our study, all the procedures in BDE were performed as EGD first with an aerosol chamber followed by colonoscopy.…”
Section: Discussionmentioning
confidence: 99%